2021
DOI: 10.1371/journal.pone.0261736
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order structure of DNA determines its positioning in cell-size droplets under crowded conditions

Abstract: Background It is becoming clearer that living cells use water/water (w/w) phase separation to form membraneless organelles that exhibit various important biological functions. Currently, it is believed that the specific localization of biomacromolecules, including DNA, RNA and proteins in w/w microdroplets is closely related to their bio-activity. Despite the importance of this possible role of micro segregation, our understanding of the underlying physico-chemical mechanism is still unrefined. Further researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…39 As a consequence, the abrupt contraction of the DNA coil, known as, “coil–globule transition” takes place at a critical PEG concentration. 40…”
Section: Resultsmentioning
confidence: 99%
“…39 As a consequence, the abrupt contraction of the DNA coil, known as, “coil–globule transition” takes place at a critical PEG concentration. 40…”
Section: Resultsmentioning
confidence: 99%
“…This spindle size scaling by the space size can be easily reproduced by confining the cell extract in droplets of different space sizes (Figure d). , Studies suggest that the scaling mechanism is explained by finite elementality and the large surface area–volume ratio . In vitro experiments with genome-size DNA showed that its membrane interaction is associated with TX–TL dynamics and the higher-ordered structure of DNA. , …”
Section: Phase Transitions Of Biochemical Activity and Higher-order S...mentioning
confidence: 91%
“…99 In vitro experiments with genome-size DNA showed that its membrane interaction is associated with TX−TL dynamics and the higher-ordered structure of DNA. 100,101 Cell-sized space also regulates higher-order structures other than genomic DNA. The spatial limitation plays a significant role in the macroscopic structure formation and function of molecules such as actin that polymerize like filaments and generate force for cell deformation.…”
Section: ■ Phase Transitions Of Biochemical Activity and Higher-order...mentioning
confidence: 99%
“…[15][16][17][18][19] We also observed that genomic DNA and DNA hydrogels were concentrated in the dextran-rich droplets, whereas short ssDNA were distributed in both dextran-rich droplets and a PEG-rich continuous phase. [20][21][22] We expected small ssDNA and large DNA structures would have different partitions and be separable by W/W-droplet fractionation (Figures 1B and 1 C). Therefore, the W/W-droplet system is expected to be applied to purify DNA structures such as DNA motifs, DNA origami, DNA hydrogel, and DNA microtubes.…”
Section: Introductionmentioning
confidence: 93%